PATTERNS OF DISTRIBUTION TOTAL SUSPENDED SOLID (TSS) IN RIVER ESTUARY KAMPAR PELALAWAN - Rozali '; Mubarak '; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in April 2016 in Kuala Kampar estuary watersPelalawan. The purpose of this study to determine the level of the distributionpattern of suspended solids in the Kampar River Estuary at high tide to the ebband flow toward the post method used in this research is survey method, namelythe study sample was obtained in the field are considered to represent the Islandwaters Mendol, then the samples were analyzed in laboratories to test TSS (TotalSuspended Solid) distribution pattern of total suspended solids in waters KamparRiver Estuary seen that the accumulation of suspended particles at low tide andthe tide heading toward downs, TSS distribution pattern is at the highest value atthe time of ebb tide toward which the values obtained range from 500-1500 mg / l,This indicates that the incoming flow pattern during ebb tide towards very high tothe north. While the TSS distribution pattern that went into the water at low tide tothe obtained value of 700-1100 mg / l where the distribution pattern heading southlocation research.Keywords: Kampar River estuary, distribution patterns TSS (Total SuspendedSolid) Tidal.